Who benefits from alcohol screening and brief intervention?: A mini-review on socioeconomic inequalities with a focus on evidence from the United States - Kilian, Carolin; Lemp, Julia M.; Probst, Charlotte (Addictive behaviors, 2023)
Alcohol-attributable mortality contributes to growing health inequalities. Addressing hazardous alcohol use and alcohol use disorders through alcohol screening and brief intervention is therefore a promising public health strategy to improve health equity. In this narrative mini-review, we discuss the extent to which socioeconomic differences exist in the alcohol screening and brief intervention cascade, highlighting the example of the United States. We have searched PubMed to identify and summarize relevant literature addressing socioeconomic inequalities in (a) accessing and affording healthcare, (b) receiving alcohol screenings, and/or (c) receiving brief interventions, focusing predominantly on literature from the Unites States. We found evidence for income-related inequalities in access to healthcare in the United States, partly due to inadequate health insurance coverage for individuals with low socioeconomic status. Alcohol screening coverage appears to be generally very low, as is the probability of receiving a brief intervention when indicated. However, research suggests that the latter is more likely to be provided to individuals with low socioeconomic status than those with high socioeconomic status. Individuals with low socioeconomic status also tend to benefit more from brief interventions, showing greater reductions in their alcohol use. Once access to and affordability of healthcare is ensured and high coverage of alcohol screening is achieved for all, alcohol screening and brief interventions have the potential to enhance health equity by reducing alcohol consumption and alcohol-related health harms.
Online veröffentlicht: 9. Juni 2023, Artikelversion: 12. Juni 2023
Gesehen am 31.10.2023